Implementation of A Volleyball Training Program through A Positive Youth Development Approach - Damayanti, Sindi; Sonjaya, Azhar Ramadhana; Kosasih, Alam Hadi (Universitas Majalengka, 2025)
Volleyball is a sport that contributes greatly to physical activity in society and plays an important role in the positive growth of youth. Sports not only improve physical abilities but also build the character of athletes. However, most sports training programs today concentrate on achieving competitive results and ignore the formation of positive values. Character development through sports is the main focus of the Positive Youth Development (PYD) approach. With the 7C approach which includes competence, self-confidence, connection, character, caring, contribution, and creativity, it is hoped that the training program can create individuals who excel in technical aspects and have positive athlete characters. This study aims to determine how the character of athletes in the volleyball sport of the ANP Garut Volleyball Club is influenced by the implementation of a volleyball training program with the Positive Youth Development (PYD) approach. The method used in this study is a quantitative method with a pseudo-experiment, namely the Non-Equivalent Control Group with the Pretest-Posttest approach. In this study, 20 volleyball athletes from the ANP Volleyball Club, Garut Regency were selected as research samples. The research instrument used a PYD-based questionnaire consisting of 49 items. Athletes were given an instrument about positive youth development 7C as a measuring tool. Data analysis was conducted using statistical tests with SPSS version 28 to process data and determine differences in pretest and posttest results. The results showed that the volleyball training program through the Positive Youth Development program approach had a significant effect between the group that participated in the PYD 7Cs-based training program and the group that was not given the PYD 7Cs program, where the experimental group showed better improvements in technical skills and character.